Prediction and Validation of 3-Dimensional Structure of Rice OsTHIC Abiotic Stress Responsive Gene (Asian Journal of Plant Biology, 2022)
Rice is an important cereal crop believed to have been cultivated for hundred years. The ancestry and evolution of this plant and its diverse cultivars remain contentious. Thus, determining the cultivar's molecular mechanism of abiotic stress-responsive genes using a bioinformatics system continues to be an area to investigate. For better knowledge of the mechanisms of the abiotic stress-responsive gene from rice, a novel stress-related gene named OsTHIC was selected for this study. The OsTHIC gene accessions were collected from NCBI, then predict its secondary structure. I-TASSER server was used to predict the 3-dimensional [3D] model of the gene protein and validated using ERRAT and Ramachandran plot. The OsTHIC gene appeared to be highly conserved and structurally functional. The secondary structure of the OsTHIC indicated a high percentage of a random coil [47.35%], followed by an alpha helix [45.05%], then an extended strand [10.61%].  The prediction using I-TASSER modeller produced structures based on the protein sequence. The protein 3D model showed different model qualities using the two-refinement software which ERRAT Plot model refinement having the best score at 97.266%.
Keywords: OsTHIC gene; Secondary structure prediction; I-TASSER; 3-D model; C-score